Factors Affecting The Customer Saving in KC Singkawang Bank Syariah Mandiri - Maulina Fera; Wui San Taslim (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2017)
This study aims to determine how much influence the product factor, quality of services provided, offered profit sharing ratio and religiosity factor customers to save customers' interest in Bank Syariah Mandiri (BSM) KC Singkawang. The research location is in Singkawang, where people Singkawang has a multi-ethnic city that consists of three (3) the largest ethnic Chinese, Malay and Dayak. This underlying this research. The method used is an associative method, the data collection technique of distributing questionnaires to the respondents to explore related information about the factors that affect customers save on BSM KC Singkawang. This research resulted in the coefficient of determination (R2) of 0443 which means that the variable products, services, revenue sharing and religiosity can explain the customer's decision in BSM KC Singkawang saving of 44.3%. While the remaining 55.7% is influenced by other factors not included in this research model.